Selective Death of Newborn Neurons in Hippocampal Dentate Gyrus Following Moderate Experimental Traumatic Brain Injury - Gao, Xiang (2008)
Memory impairment is one of the most significant residual deficits following traumatic brain injury (TBI) and is among the most frequent complaints heard from patients and their relatives. It has been reported that the hippocampus is particularly vulnerable to TBI, which results in hippocampus-dependent cognitive impairment. There are different regions in the hippocampus, and each region is composed of different cell types, which might respond differently to TBI. However, regional and cell type-specific neuronal death following TBI is not well described. Here, we examined the distribution of degenerating neurons in the hippocampus of the mouse brain following controlled cortical impact (CCI) and found that the majority of degenerating neurons observed were in the dentate gyrus after moderate (0.5 mm cortical deformation) CCI-TBI. In contrast, there were only a few degenerating neurons observed in the hilus, and we did not observe any degenerating neurons in the CA3 or CA1 regions. Among those degenerating cells in the dentate gyrus, about 80% of them were found in the inner granular neuron layer. Analysis with cell type-specific markers showed that most of the degenerating neurons in the inner granular neuron layer are newborn immature neurons. Further quantitative analysis shows that the number of newborn immature neurons in the dentate gyrus is dramatically decreased in the ipsilateral hemisphere compared with the contralateral side. Collectively, our data demonstrate the selective death of newborn immature neurons in the hippocampal dentate gyrus following moderate injury with CCI in mice. This selective vulnerability of newborn immature dentate neurons may contribute to the persistent impairment of learning and memory post-TBI and provide an innovative target for neuroprotective treatment strategies.